2007
DOI: 10.1111/j.1745-4549.2007.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Fermentation of Sweet Potato (Ipomoea Batatas L.) Into Pickles

Abstract: Lactic acid (LA) fermentation has many benefits. It is feasible in small scale, inexpensive, and does not require additives and confers organoleptic characteristics to the foodstuff according to the habits and requirement of the consumers. Sweet potato roots were pickled by lactic fermentation by brining the cut and blanched roots in common salt (NaCl, 2–10%) solution and subsequently inoculated with a strain of Lactobacillus plantarum (MTCC 1407) for 28 days. The treatment with 8–10% brine solution was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 31 publications
3
38
0
2
Order By: Relevance
“…In a different study, van Jaarsveld, Marais, Harmse, Nestel, and Rodriguez-Amaya (2006) reported losses of close to 20%. (Panda, Parmanick, & Ray, 2007) observed about 22.2% losses in a selected Indian OFSP after blanching for 15mins at 100ºC. However, they reported a less than significant change in β-carotene in the varieties processed by fermentation.…”
Section: Introductionmentioning
confidence: 95%
“…In a different study, van Jaarsveld, Marais, Harmse, Nestel, and Rodriguez-Amaya (2006) reported losses of close to 20%. (Panda, Parmanick, & Ray, 2007) observed about 22.2% losses in a selected Indian OFSP after blanching for 15mins at 100ºC. However, they reported a less than significant change in β-carotene in the varieties processed by fermentation.…”
Section: Introductionmentioning
confidence: 95%
“…Several groups have reported the fermentation of pickled sweet potatoes without inoculation with a mixed culture (Panda et al 2007;Panda et al 2009;Sivakumar et al 2010;Yuliana and Nurdjanah 2009;and Yuliana et al 2010). So far there is no report mentioning the effect of inoculation with bacterial cultures commonly used for pickle processing, such as Leuconostoc mesenteroides and Lactobacillus plantarum, on the characteristics of pickled sweet potatoes.…”
Section: Methodsmentioning
confidence: 99%
“…The carotenoid content of orange-fleshed sweet potatoes has been reported around 18 mg/100 g fresh weight (Panda et al 2007). This potential character of orangefleshed sweet potatoes should be responded by many food manufacturers to produce a healthy food.…”
mentioning
confidence: 99%
“…Microbial strains that produce pectinase enzyme are thus required for cassava tissue disintegration. Good pH reduction (a fast lowering of the pH) is important to accelerate fermentation process as well as reduce the levels of contaminating microorganisms which can compete with the starters for nutrients (Holzapfel, 2002) and also a critical factor in developing flavour and aroma of foods (Montet, Loiseau, & Zakhia-Rozis, 2006;Panda, Parmanick, & Ray, 2007). Acidification in growth medium as monitored showed decrease in values with increase in incubation time, ranging from a starting pH of 6.50 to 3.58 after 72 hours incubation.…”
Section: Ijfs April 2016 Volume 5 Pages 61-72mentioning
confidence: 99%